Impactos de um governo com características liberais no crescimento e bem-estar do Brasil: uma análise de equilíbrio geral - Rola, Pedro Henrique Ferreira (2019)
This paper aims to construct a general equilibrium model, in order to simulate the policies of a liberal-conservative government, with privatization of state companies, reduction of the public debt of the state and reduction of the tax burden, aiming to verify its effects. macroeconomic aggregates and social welfare. To analyze these effects, a government-based closed-economy neoclassical model was adopted, following the calibration and specification used in several studies, such as Santana et al. (2012), Campos and Pereira (2016) and Bezerra et al. (2018). The parameters used in the model were obtained from a general mapping between the Brazilian national accounting data and the model variables. The privatization policy used in the model addresses the transfer of state-owned capital stock to reduce the share of state public debt in the economy. While the reduction of the tax burden used sought to approximate the discourse of the economic team, reducing the tax rates present in taxation. The simulation of the implementation of the privatization policy together with the reduction of the tax burden shows that the welfare effect is positive and there is an improvement in the macroeconomic aggregates in the short and long term, showing the impact It is positive that there is a decrease in government consumption and thus a reduction in the size of the state in the economy.